Laboratory Study on Changes in Gas Desorption Properties of Anthracite after Cyclic Loading - Tie Li; Dong Wang; Mei-Hua Liu; Liang Chen; Hao Liu (Advances in Civil Engineering)
Coal mass is subjected to cyclic loading during pulsating hydraulic fracturing (PHF), and changes in its gas desorption properties affect gas drainage. Therefore, it is of great importance to correctly understand the influences of cyclic loading on the gas desorption properties of coal mass. Firstly, loading tests with different frequencies and amplitudes were performed on anthracite from Qinshui Basin (Shanxi Province, China) using a fatigue testing machine. Secondly, gas desorption tests were performed to determine the associated curves for each test group at different equilibrium pressures, and the initial desorption capacity and diffusion coefficient of the gas were calculated. Finally, the influence of different loading conditions on the gas desorption laws were analyzed. The test results demonstrate that a greater loading frequency increases the ratio of the initial desorption capacity so that the desorption rate of coal samples is higher, and the gas desorption properties become increasingly better in the initial stage. However, variations in the amplitude have minimal impact on the ratio of the initial desorption capacity. When the amplitude is too large in the initial stage, the diffusion coefficient decreases and the gas desorption properties worsen. In addition, the above test results are used to discuss the selection of the amplitude and frequency in the PHF process from a macroperspective. The contained research results provide an important theoretical basis for the field application of PHF technologies in coal mines.